Modified Hypoallergenic Filtering Medium for Potential use in Face Masks: A Systematic Review - Baldoz, Julianne Isabel B. (Animo Repository, 2022)
The COVID-19 pandemic has affected numerous lives and lifestyles of people around the world. In response, governing bodies worldwide have imposed public health protocols such as requiring their residents to wear face masks. To lessen the impacts of COVID-19, it is necessary to strengthen the public’s main protective equipment by having a face mask that can provide better filtration and protection to the user. This research aims to propose an electrospun hypoallergenic bi-layer material composed of a layer of CS/PVA composite and a sheet of PCL that could be used in face masks in the future. The polymers chitosan (CS), polyvinyl alcohol (PVA), and polycaprolactone (PCL) were selected to be potential replacements for the commonly-used polypropylene (PP). The polymer replacements were selected through a systematic review designed to assess various factors such as language, date, credibility, subject area, article type, and reported outcome. For the hydrophilic inner filter layer, CS was combined with PVA while PCL was selected for the hydrophobic outer layer. The preliminary and final screening of 1014 studies resulted in 4 studies that served as the basis for the proposed materials, preparation process, and fabrication process that compose the protocol of the mask filter.